Managing building checkist plans Using BUSCLIS - Muhammad Zulfahmi Toh, Abdullah; Noraziah, Ahmad; Mohammad Affendy, Omardin; Nursharina, Zainuddin (Penerbit UMP, 2016)
This paper presents the software namely Building Submission Checklist System (BUSCLIS). It has been developed to manage the submission of building checklist plans process in the construction industry. BUSCLIS helps to simplify the management for acquiescence data of building plan approval for the Local Authority (LA) and Country Planning in Malaysia through the web based system. BUSCLIS facilitates user through the computerization forms, which provides fast, efficient and effective service to the engineer, architect and contractor. Relevant and timely information manage by sophisticated BUSCLIS with the database management system MySQL.